IMPLEMENTASI TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGS) DI DESA WARBAL, KEI KECIL BARAT, MALUKU TENGGARA - Dwi Partini; Asrul Asrul; Elma Thiansi Masbaitubun (Universitas Nusa Cendana, 2025)
This study aims to analyze the implementation of Sustainable Development Goals (SDGs) in Desa Warbal, Kei Kecil Barat, Southeast Maluku, focusing on achievements and challenges faced within the local context. A descriptive qualitative approach was employed, involving in-depth interviews, focus group discussions, participatory observations, and document analysis. The findings reveal that Desa Warbal has made significant progress in the social and economic development pillars, including poverty alleviation, food security, healthcare services, quality education, and basic infrastructure development. However, achievements in environmental and governance pillars remain limited. Key issues include limited access to clean energy, ineffective management of marine and terrestrial environments, vulnerability of settlements to tidal floods, and static village institutions with minimal external partnerships. Internal social conflicts also hinder peaceful and just governance. These findings underscore the importance of holistic and contextual policy interventions, strengthening village institutional capacity, and increasing community participation to ensure comprehensive and sustainable SDGs implementation. This study contributes empirical insights into the dynamics of SDGs implementation in Indonesian coastal villages with unique geographic and social characteristics and provides strategic recommendations for sustainable development policy at the local level